THE ROLE OF EMOTIONAL INTELLIGENCE IN THE INTERACTION OF PARTICIPANTS OF THE EDUCATIONAL PROCESS OF A HIGHER EDUCATIONAL INSTITUTION - CHERVINSKA, Inna; HALIUK, Nadia; MERGEL, Tetyana (Mountain School of Ukrainian Carpaty, 2025)
The authors reveal the essence of the concept of «emotional intelligence» and analyze the words "intelligence" and its various cognitive characteristics. The article states that for effective online communication in the educational environment of a higher education institution, all participants in the educational process must have, in addition to a high level of communicative speech culture and culture of communication, an appropriate level of emotional intelligence. It is emphasized that developed emotional intelligence during stressful situations in wartime contributes to teamwork of students, the establishment of individual development of each, the prevention of conflict situations, emotional burnout. In general, the development of emotional intelligence plays an important role in creating a positive environment during war and conflicts. Among the leading aspects of the emotional intelligence of participants in the educational process, the article identifies the following: emotional self-regulation; empathy, the ability to resolve conflicts, communication skills and stress resistance. It is emphasized that the development of emotional intelligence depends on the cognitive characteristics of the individual, on the formation of understanding of the essence and meaning of emotions, on the developed skills of emotional response. Based on the conducted content analysis of scientific psychological and pedagogical literature and observations of the organization of training, the authors determined the role and place of emotional intelligence in the system of communicative interaction of participants in the educational process during the war, revealed the positive qualities of this interaction. It is indicated that during the work on the organization of the study, a complex of general scientific methods was used, which made it possible to determine the key aspects of the problem of the development of emotional intelligence. Empirical methods were used to collect scientific and research material, conversations with scientific and pedagogical workers regarding their readiness to implement ideas, forms and models of applying emotional intelligence technologies in the educational process of modern educational institutions.